2020
DOI: 10.1177/1362168820928577
|View full text |Cite
|
Sign up to set email alerts
|

The effects of structured input and traditional instruction on the acquisition of the English causative passive forms: An eye-tracking study measuring accuracy in responses and processing patterns

Abstract: The present study explores the effects of structured input and traditional instruction on the acquisition of English causative passive forms using online measurements (eye-tracking). Previous empirical research investigating the effects of processing instruction through offline measurements (sentence and discourse) has overall shown positive results for this pedagogical intervention. Research investigating the main factor responsible for the effectiveness of processing instruction has confirmed that it is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…For example, an eye-tracking study by Wong and Ito (2018) found that PI led learners to reject a first-noun interpretation of causative faire constructions in French. Similarly, Benati (2020c) found that, after PI, learners' eye movements showed smaller first noun bias and faster picture selection while they processed English causative passive sentences. Lee and Doherty (2019) found that PI directed learners' attention to grammatical information on Spanish verbs marked for the passive voice and noted that learners' processing became more native-like after instruction.…”
Section: Interpreting the Effects Of Pimentioning
confidence: 81%
See 2 more Smart Citations
“…For example, an eye-tracking study by Wong and Ito (2018) found that PI led learners to reject a first-noun interpretation of causative faire constructions in French. Similarly, Benati (2020c) found that, after PI, learners' eye movements showed smaller first noun bias and faster picture selection while they processed English causative passive sentences. Lee and Doherty (2019) found that PI directed learners' attention to grammatical information on Spanish verbs marked for the passive voice and noted that learners' processing became more native-like after instruction.…”
Section: Interpreting the Effects Of Pimentioning
confidence: 81%
“…Studies on PI and related instructional trainings that employ online processing measures are still relatively few (see Benati, 2020b), but several recent studies have used these methods given the detail they provide. As discuss, these studies have investigated a diverse range of questions, including the effects of PI (or related trainings) versus other types of instruction or no-training controls (Benati, 2020c(Benati, , 2020aChiuchiù & Benati, 2020;Issa & Morgan-Short, 2019;McManus & Marsden, 2017Wong & Ito, 2018); EI and feedback (Dracos & Henry, 2018;Wong & Ito, 2018), input enhancement (Issa & Morgan-Short, 2019), the modality of training (Ito & Wong, 2019), and the role of individual differences such as working memory (Dracos & Henry, 2021;Issa, 2019;.…”
Section: Interpreting the Effects Of Pimentioning
confidence: 99%
See 1 more Smart Citation
“…Benati points out that more research is needed to measure implicit knowledge adopting psycholinguistic and neurolinguistic research tools (online tests). He illustrates this with an example of a focus on form study adopting eyetracking measurement (Benati, 2020). The final section summarizes the key points in this part.…”
Section: Alessandro Benatimentioning
confidence: 95%
“…Benati points out that more research is needed to measure implicit knowledge adopting psycholinguistic and neurolinguistic research tools (online tests). He illustrates this with an example of a focus on form study adopting eye‐tracking measurement (Benati, 2020). The final section summarizes the key points in this part.…”
mentioning
confidence: 99%